2022
DOI: 10.3389/fphar.2022.883103
|View full text |Cite
|
Sign up to set email alerts
|

Less Timely Initiation of Glucose-Lowering Medication Among Younger and Male Patients With Diabetes and Similar Initiation of Blood Pressure-Lowering Medication Across Age and Sex: Trends Between 2015 and 2020

Abstract: Aims: We aimed to assess trends in glycosylated hemoglobin A1c (HbA1c) and systolic blood pressure (SBP) thresholds at initiation of glucose- and blood pressure-lowering medication among patients with type 2 diabetes and assess the influence of age and sex on these trends.Materials and Methods: We used the Groningen Initiative to ANalyze Type 2 diabetes Treatment (GIANTT) primary care database. Patients initiating a first non-insulin glucose-lowering or any blood pressure-lowering medication between 2015 and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…A Dutch study found an upward trend in mean HbA1c at the time of the first use of diabetes medication, from 7.4% in 2015 to 8.0% in 2020 [22] . Although HbA1c was highest in 2020, this could be due to a continuation of the already present trend or due to delayed diagnosis of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…A Dutch study found an upward trend in mean HbA1c at the time of the first use of diabetes medication, from 7.4% in 2015 to 8.0% in 2020 [22] . Although HbA1c was highest in 2020, this could be due to a continuation of the already present trend or due to delayed diagnosis of diabetes.…”
Section: Discussionmentioning
confidence: 99%